Revisited the potential risks of carcinogenicity of phototherapy in patients with psoriasis - A. A. Kubanov; M. B. Zhilova (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The article presents published data on the assessment of the risk of cancerogenicity of multiple courses of phototherapy methods such as PUVA therapy and UVB-311 in psoriatic patients. The authors analyzed the incidence of malignant skin neoplasms (squamous cell carcinoma, basal cell carcinoma, malignant skin melanoma) among psoriatic patients from different population groups taking into account the cumulative radiation doses and number of procedures.